Change of forest land use based on conservation policy and practice: a case study in Danum Valley, Malaysia - Normah Abdul Latip; Scofield Roystones Steven; Rahmah Rashid; Rehmat Karim; Mohd Umzarulazijo Umar; Rosazman Hussin; Mohamad Pirdaus Yusoh; Jeannet Stephen; Christina Andin; Nor-Ina Kanyo (Malaysia Institute of Planners, 2022)
Southeast Asia’s forest and green areas are undergoing a fast and substantial experienced sudden change, depending on complex area management issues resulting in deforestation, including Danum Valley, Sabah, Malaysia. The study purposely to determine the land-use pattern at Danum Valley through a geospatial approach. GIS data was collected from government official departments such as the Sabah Forest Department and Urban and Regional Planning Sabah Department. Land-use changes analysis, namely Relative land use percentages and matrix analysis used to understand the changing pattern and current scenario of land use activity at Danum Valley. Preliminary findings indicate a change of forest land use from Class 2 Commercial Forest Reserve into Class 1 Protected Forest Reserve during the three times series within an area of influence near Danum Valley.